ҲӘЗИРГИ ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ҚЫСҚАРҒАН АТЛЫҚЛАРДЫҢ ЛИНГВИСТИКАЛЫҚ АНАЛИЗИ - Опаева, Р.А. (FAN va JAMIYAT, 2017)
The article deals with the ussues of using short nouns which appear in the modern Karakalpak language. There has been made a scientific analysis of short nouns connected with changes in science and technology as well as in the society. One of the main tasks today is the scientific analysis of short nouns and their systematization.